Downregulation of cytoplasmic DNases is implicated in cytoplasmic DNA accumulation and SASP in senescent cells - Akiko Takahashi (Nature Portfolio, 2018)
Activation of DNA damage response induces the acquisition of senescence-associated secretory phenotype (SASP) in senescent cells, but precise mechanisms remain unclear. Here, the authors show that the cytoplasmic accumulation of nuclear DNA activated cytoplasmic DNA sensors to provoke SASP.